Substituição do farelo de soja por ureia em dietas a base de palma forrageira (Opuntia ficus indica Mill) para cabras em lactação - Neves, Romildo da Silva (2016)
The aim of this study was made to evaluate the influence of the substitution of soybean by urea in diets based on cactus pear cladodes. The variables studied were food intake, digestibility, milk production and parameters about rumen and blood. The experiment was carried out at the experimental station of small ruminant of the UFPB, located at São João do Cariri municipality, Paraiba state. Twelve crossbreed goats with 30 days of lactation and average body weight of 50 ± 2 kg were used. Animals were distributed in a Latin square with 4 periods, 4 diets and 3 animals per diet (4x4x3). Diets were composed by Tifton grass, cactus pear cladodes and concentrate. Treatments were considered as levels of urea substitution (0.0, 0.65, 1.3 and 1.95%). Nutrient intake, digestibility, ruminal pH, volatile fatty acids concentration, milk yield and composition were not influenced by the use of urea. The total water intake was reduced as the levels of urea were creased. The microbial protein production, measured 4 hours after feeding, was reduced linearly with the replacement of soybean in its meal. The blood metabolites were evaluated, but only phosphorous, albumin and glucose were influenced by the substitution. It could be used up to 1.95% of urea replacing soybean meal in the diet of lactating goats without altering milk yield and composition.